Gender influence on emotional perception of wheelchair users based on self-report and facial micro-expression - De Lima Lanutti, Jamille Noretza [UNESP]; Pereira, Douglas Daniel [UNESP]; Medola, Fausto Orsi [UNESP]; Paschoarelli, Luis Carlos [UNESP] (Associacao Pro-Ensino Superior em Novo Hamburgo, 2021)
People with disabilities are socially characterized by their limitations and assistive devices. In particular, the Wheelchair (CR) is an Assistive Technology seen as socially limiting. This can influence the emotional experience with these stigmatized products. This study sought to understand how gender influences the emotional perception of CR users from the analysis of two different methodological tools: Self-report (EMOG) and physiological (FaceReader®). Twenty CR users participated in the study, 10 male and 10 female (mean age 41.76 years and SD 11.34). Thus, it was possible to qualify and quantify the emotion of these users, and the results achieved with the present study allow us to state that both Emog and FaceReader® identify that male participants demonstrate more positive emotions and with greaterintensity, when compared to participants of the female gender.
Influência do gênero na percepção emocional de usuários de cadeiras de rodas a partir do autorrelato e microexpressão facial
Keywords: Emotional Design; Facial Micro-expression; Wheelchairs